THE STUDENTS’ COMPREHENSION ON THE PHILOSOPHY OF MATERNITY CARE “WOMEN CENTERED CARE” BASED ON THE REPORT OF CONTINUITY OF CARE (COC) - Rr Sri Nuriaty Masdiputri; Darmayanti Wulandatika (LPPM - Universitas Muhammadiyah Banjarmasin, 2019)
Background: The mortality rate of maternal woman in Indonesia has significantly increased reaching 359 per 100.000 live births. One solution to decrease the number of mortality rate of maternal woman is through high quality maternity care. The qualified midwifes come from a standard of education based on the philosophy of maternity care. Continuity care (COC)maternal clinic model of learning is proven in giving wide chances for the student to learn the philosophy. Objectives: reveals the level and form of students’ comprehension toward the maternity care “woman centered care”philosophy, the application of PKK-CoC, and the quality of maternity careCoC in STIKES Estu Utomo Boyolali. Method: this study is carried under mixed method and sequential explanatory strategy. The quatitative parts are fulfilled by the use of analitic descriptive design, while the quantitative side is carried under case study design. The population and sample of this study is 55 students of STIKES Estu Utomo Boyolali who have taken PKK-CoC. The sample for qualitative design is taken using mixed purposive sampling which are criterion and intensity sampling. Result: qualitatively, students overall comprehension is good. However, the documentation of maternity carein partnership care is still ineffective. Quantitatively, students overall comprehension on personalized care, holistic care, collaborative care, and evidence based care is also good. Partnership care is the only aspect considered in effective. Conclusion: the maternitycare continuity of care shows that client and family are in good heatlth, all the caregiven shows zero mortality rate, client fells safe and comfortable, and client has correct and fast care. It is also found that students’ confidence, skills, and comprehension are increased. It is suggested that the stakeholder can include the PKK-CoC model into curriculum of midwife education